Kajian Yuridis Terhadap Merek Sebagai Jaminan Pada Lembaga Perbankan - Dewi Asri Jayanto (Fakultas Hukum Universitas Mataram, 2017)
The purpose of this research is to analyze the brand setting as guarantee according to positive law in Indonesia and to analyze the brand can be used as credit guarantee in banking. The research method used in the writing of this thesis is a normative legal research that examines the positive law or legislation applicable in Indonesia relating to the guarantee and the brand. Approach method used is approach of legislation, comparative and conceptual. The analysis was done by using interpretation and analogy method. The result show that; First, Brand as a guarantee has not been regulated specifically and clearly in positive law in Indonesia, it is generally regulated in brand laws and geographical and fiduciary guarantee laws. Secondly, the Bank has not been able to accept the mark as the main guarantee, because the legal basis of the brand as an unclear guarantee which will have an impact on execution, in addition to the nature of a brand that can not be assured to the existence becomes on of the constraints of brand acceptance as a guarantee in the institution banking.